Association of visual acuity with educational outcomes: a prospective cohort study. Issue 11 (18th January 2019) - Jan, Catherine; Li, Shi-Ming; Kang, Meng-Tian; Liu, Luoru; Li, He; Jin, Ling; Qin, Xuezheng; Congdon, Nathan; Wang, Ningli
Abstract : Background/aim: To quantify the impact of baseline presenting visual acuity (VA), refractive error and spectacles wear on subsequent academic performance among Chinese middle school children. Methods: A prospective, longitudinal, school-based study on grade 7 Chinese children (age, mean±SD, 12.7±0.5 years, range=11.1–15.9) at four randomly selected middle schools in Anyang, China. Comprehensive eye examinations including cycloplegic autorefraction were performed at baseline, and information on demographic characteristics, known risk factors for myopia and spectacle wear was collected. Academic test scores for all subjects in the curriculum were obtained from the local Bureau of Education. Main outcome measure was total test scores for five subjects at the end of grade 9, adjusted for total scored at the beginning of grade 7. Results: Among 2363 eligible children, 73.1% (1728/2363) had seventh grade test scores available. 93.9% (1623/1728) completed eye examinations, and 98.5% (1599/1623) of these had ninth grade test scores. Adjusting only for baseline test score, the following were significantly associated with higher ninth grade scores: younger age, male sex, less time outdoors, better baseline presenting VA, higher parental education and income and parental myopia, but refractive error and spectacle wear were not. In the full multivariate model, baseline test score (p<0.001), presenting VA (p<0.01), age (p<0.001), quality of life (p<0.05) and parental education (p<0.001) and myopia (either: p<0.05; both: p<0.05) remained significantly associated with better ninth grade scores. Conclusions: In this longitudinal study, better presenting VA, but not cycloplegic refractive error or spectacle wear, was significantly associated with subsequent academic performance.